Transforming Social Studies Learning in MI/SD through the Integration of Problem-Based Learning and Augmented Reality to Strengthen HOTS: A Literature Review: English - Julianda; Ahmad Fauzi; Indri Yani; Moh. Amiruddin Bin Haji Abd. Rahman (International Journal of Education, Language, and Social Science, 2026)
Social Studies (IPS) learning at the Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels continues to face challenges, including teacher-centered instruction, memorization-oriented learning, limited contextual experiences, and the underutilization of educational technology to foster Higher Order Thinking Skills (HOTS). These conditions highlight the need for a learning transformation that integrates innovative pedagogy with digital technology. This study aims to analyze the transformation of Social Studies learning through the integration of Problem-Based Learning (PBL) and Augmented Reality (AR) as a conceptual approach to strengthening students’ HOTS. The study employed a library research design using a systematic literature search conducted between January and April 2026 across Google Scholar, Scopus, ERIC, ScienceDirect, and SpringerLink. Following predefined inclusion and exclusion criteria, 38 relevant publications published between 2020 and 2026 were selected through identification, screening, eligibility assessment, and qualitative conceptual synthesis. Data were analyzed using content analysis to identify recurring themes and conceptual relationships among learning transformation, PBL, AR, and HOTS. The synthesized literature suggests that integrating PBL and AR provides complementary pedagogical and technological support for creating more contextual, interactive, collaborative, and student-centered Social Studies learning environments that encourage higher-order thinking. The reviewed evidence further indicates that the successful implementation of this approach depends not only on instructional innovation but also on teachers’ pedagogical competence, technological readiness, and institutional support. Overall, the literature synthesis provides a conceptual framework that may inform future instructional practices and empirical research on technology-enhanced Social Studies learning at the MI/SD level.